Peran KNEKS dan Master Plan Ekonomi Islam Indonesia - Arifudin Arifudin; Muhammad Syahrul Rizqi; Dicky Andi Saputra; Muhammad Khairul Nizam; Ilyasa Ilyasa (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The National Committee for Sharia Economy and Finance (KNEKS) is an independent non-structural institution established in 2016. KNEKS has a focus on making economic development efforts to support the improvement of economic growth and the quality of its human resources. The National Committee of Finance and Sharia (KNEKS) is mandated to expand, and advance the development of the Islamic economy in order to support a development. This research uses qualitative methods by applying qualitative descriptive methods. At the Plenary Meeting of the National Committee for Sharia Finance (KNKS) on February 5, 2018, the President of the Republic of Indonesia directed KNKS stakeholders to prepare a Sharia Economic Master Plan that focuses on the development of the real sector of the Islamic economy or known as the halal industry. This is done to encourage the development of Islamic finance that supports national economic development. The role of Islamic finance cannot stand alone without the development of the real sector. Therefore, it is considered necessary to compile an Indonesian Sharia Economic Masterplan that can be a reference in the development of the Islamic economy in the country.